2017
DOI: 10.1038/s41598-017-13720-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine control of chlorophyll-carotenoid interactions defines the functionality of light-harvesting proteins in plants

Abstract: Photosynthetic antenna proteins can be thought of as "programmed solvents", which bind pigments at specific mutual orientations, thus tuning the overall energetic landscape and ensuring highly efficient light-harvesting. While positioning of chlorophyll cofactors is well understood and rationalized by the principle of an "energy funnel", the carotenoids still pose many open questions. Particularly, their short excited state lifetime (<25 ps) renders them potential energy sinks able to compete with the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 69 publications
8
77
4
Order By: Relevance
“…4a, we resolve the initial rise of Car S 1 ESA, characteristic of a directional energy transfer rather than a delocalized Car-Chl excited state of the excitonic mixing model. Theoretically predicted timescales for this energy transfer pathway are >20 ps due to the optically forbidden nature of the Car S 1 state 43,66,67 , which is two orders of magnitude longer than the sub-ps (<400 fs) timescale observed in our experiment. This discrepancy suggests that a more complex picture is required, such as directional Chl → Car energy transfer mediated by partial mixing of the excited states, along the lines of previous proposals 11,12,19 .…”
Section: Discussioncontrasting
confidence: 47%
“…4a, we resolve the initial rise of Car S 1 ESA, characteristic of a directional energy transfer rather than a delocalized Car-Chl excited state of the excitonic mixing model. Theoretically predicted timescales for this energy transfer pathway are >20 ps due to the optically forbidden nature of the Car S 1 state 43,66,67 , which is two orders of magnitude longer than the sub-ps (<400 fs) timescale observed in our experiment. This discrepancy suggests that a more complex picture is required, such as directional Chl → Car energy transfer mediated by partial mixing of the excited states, along the lines of previous proposals 11,12,19 .…”
Section: Discussioncontrasting
confidence: 47%
“…Nowadays, different LHC genes from plants, i.e., LHCII Balevičius et al 2017;Thallmair et al 2019), CP29 (Ioannidis et al 2016;Papadatos et al 2017) and PsbS Liguori et al 2019), have been simulated up to the μs timescale with atomistic resolution. Most of these works have focused in particular on characterizing how the interactions among the Chls and Cars bound to LHCs change depending on the different protein conformations sampled via MD (Liguori et al 1 3 2015; Balevičius et al 2017;López-Tarifa et al 2017;Maity et al 2019). This is of particular interest because a change of interactions among Chls or between Chls and Cars can lead to creation or disruption of quenching sites inside the LHCs or can change their spectral properties.…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 99%
“…On the contrary, it was shown that QM methods are necessary to accurately describe changes in Chl-Car couplings along an MD trajectory. Ab initio protocols have been recently developed to compute Chl-Car couplings and also, more specifically, predict the activation of quenching in LHCs (Duffy et al 2013;Balevičius et al 2017;Fox et al 2017;Maity et al 2019). A brief overview of studies using MD simulations in combination with QM methods will be given in Sect.…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 99%
“…In order to asses the efficiency of quenching within the dimer and LHCII a suitable measure is needed. Here, as previously (Chmeliov et al 2015;Fox et al 2017Fox et al , 2018Balevičius Jr. et al 2017), we consider the 'mean excitation lifetime', exc . This is an observable quantitiy (through fluorescence lifetime/yield measurements) and is therefore basis-independant.…”
Section: Excitation Lifetimes and Dynamics Within A Coupled System Ofmentioning
confidence: 99%